Attitudes and beliefs toward the use of stereotactic body radiotherapy in oligometastatic breast cancer: A commentary on a survey of Canadian Medical Oncologists. Issue 6 (1st July 2019) - Donovan, Elysia; Dhesy‐Thind, Sukhbinder; Mukherjee, Som; Kucharczyk, Michael; Swaminath, Anand
Abstract: Stereotactic body radiotherapy (SBRT) is a highly ablative local therapy which has emerged as part of the treatment paradigm for patients with oligometastatic (OM) breast cancer (defined by 5 or fewer sites). This patient group has demonstrated improved prognosis in some cases and may therefore, benefit from aggressive local treatment. The role of upfront SBRT in newly diagnosed OM breast cancer in addition to systemic therapy is not clear, yet it is being increasingly utilized within the oncology community. The Canadian medical system is an ideal platform in which to investigate SBRT into the OM breast cancer setting, as it is not routinely implemented across centers at this time, as there is potential for robust collaboration between oncologists in the small community to investigate SBRT, and there is limited financial or industry motivation for early SBRT uptake compared with other countries. It is critical therefore to define the optimal patient population and scenarios for which SBRT should be investigated, as well as offered in the interim to Canadian patients. We therefore conducted a survey of Canadian Medical Oncologists, the primary physicians and gatekeepers of patients with OM breast cancer, to characterize their beliefs, opinions, and areas of controversy in the use of SBRT for OM breast cancer.